Crystallization and preliminary X‐ray diffraction analysis of the interleukin‐3 alpha receptor bound to the Fab fragment of antibody CSL362. Issue 3 (1st March 2014) - Broughton, Sophie E.; Hercus, Timothy R.; Nero, Tracy L.; Dhagat, Urmi; Owczarek, Catherine M.; Hardy, Matthew P.; Fabri, Louis J.; Scotney, Pierre D.; Nash, Andrew D.; Wilson, Nicholas J.; Lopez, Angel F.; Parker, Michael W.
<x xml:space="preserve">Abstract</x> Interleukin‐3 (IL‐3) is a member of the beta common family of cytokines that regulate multiple functions of myeloid cells. The IL‐3 receptor‐specific alpha subunit (IL3Rα) is overexpressed on stem cells/progenitor cells of patients with acute myeloid leukaemia, where elevated receptor expression correlates clinically with a reduced patient survival rate. The monoclonal antibody (MAb) CSL362 is a humanized MAb derived from the murine MAb 7G3, originally identified for its ability to specifically recognize the human IL‐3 receptor and for blocking the signalling of IL‐3 in myeloid and endothelial cells. In order to elucidate the molecular mechanism of CSL362 antagonism, a preliminary structure of human IL3Rα in complex with the MAb CSL362 has been determined.